Developing a framework for understanding the relationship between religion and videogames - Ferdig, Richard E. (Online - Heidelberg journal of religions on the internet, 2014)
Religion is either explicitly or implicitly found in videogames. In some cases, the player acts as a god or must defeat a demigod or set of demons. In other cases, religious aspects are less transparent, serving as an environmental factor or background to a particular game rule or mechanic. The purpose of this paper is to first acknowledge the potential impact of those intentional and unintentional pedagogical strategies and outcomes inherent in games. It then sets out to further explore how and what people learn about religion while playing; it also addresses how religion changes game play. Finally, although there is value in deeper case studies of specific games, this article takes a holistic approach to understanding games and religion. It does so by presenting a framework of four key areas where religious themes prevail: game content, game context, game challenge, and player capital.